2023
DOI: 10.3390/risks11020046
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy Confidence and Retirement Planning: Evidence from China

Abstract: Though ample empirical evidence demonstrates the relationship between objective financial literacy and retirement planning, we have a limited understanding of the role of individuals’ subjective financial literacy in their retirement planning. In this study, we examine how individuals’ financial literacy confidence bias affects their retirement planning behaviors using survey data in China. Based on the difference between respondents’ subjective and objective financial literacy from survey data, we construct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Irrespective of the differences in confidence disposition, the results indicated that overconfidence in financial literacy can encourage one to invest in stocks and prepare for retirement, which are consistent with previous studies investigating the same research questions (Allgood and Walstad 2016;Xia et al 2014), and between overconfidence and retirement preparation (Chen et al 2019;Rooij et al 2012). As can be seen in Table 5, among those with low objective financial literacy (OFL), the overconfident type was 10.6% more likely to have a retirement plan than their low OFL peers, while among those with high OFL, the underconfident type was 15.6% less likely to do so than their high OFL peers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Irrespective of the differences in confidence disposition, the results indicated that overconfidence in financial literacy can encourage one to invest in stocks and prepare for retirement, which are consistent with previous studies investigating the same research questions (Allgood and Walstad 2016;Xia et al 2014), and between overconfidence and retirement preparation (Chen et al 2019;Rooij et al 2012). As can be seen in Table 5, among those with low objective financial literacy (OFL), the overconfident type was 10.6% more likely to have a retirement plan than their low OFL peers, while among those with high OFL, the underconfident type was 15.6% less likely to do so than their high OFL peers.…”
Section: Discussionsupporting
confidence: 88%
“…Rooij et al (2012) found that overconfidence is conducive to preparation for retirement but has no effect on wealth accumulation, while underconfidence has no effect on either outcome. It was also found that overconfidence leads to stock market participation or retirement planning (Allgood and Walstad 2016;Chen et al 2019;Chu et al 2017;Xia et al 2014). While Ooijen and Rooij (2016) found no effect of overconfidence on risk-taking decisions involving mortgages, Asaad (2015) documented that overconfident individuals have a higher propensity to engage in risky or costlier financial behaviors.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Moreover, subjective FL is found to positively affect the magnitude of savings and investment decisions in risky assets (Tang and Baker, 2016). Chen andChen (2023), V€ or€ os et al (2021) and Henager and Mauldin (2015) also acknowledge that subjective FL is one of the significant predictors of savings behaviours among individuals. The underlying reason may be the ability of FC to capture psychological factors which remain unobserved in the traditional FL test (Bellofatto et al, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…As farm owners generally hold large landholdings, they enjoy access to various loans and other financial services from formal financial institutions (Hussain and Thapa, 2012). The formal credit is used for procuring seeds, pesticides, agro machineries and creating agro infrastructure for farming operations which in turn enable them to earn and save consistently (Chen and Chen, 2023). Further, large farmers can have the benefits of crop diversification, which enables them to earn and save regularly throughout the year (Baba and Abdulai, 2021).…”
Section: Fl Fc and The Savings Behaviour Among The Indian Farmersmentioning
confidence: 99%
See 1 more Smart Citation